Cisplatin hepatotoxicity mediated by mitochondrial stress. (2nd October 2015) - Waseem, Mohammad; Bhardwaj, Monica; Tabassum, Heena; Raisuddin, Sheikh; Parvez, Suhel
Abstract: Context : Chemotherapy has long been the keystone of cancer regimen, and comprehensive research has been done on the development of more potent and less toxic anti-cancer agents. Cisplatin (CP) is a potent and extensively used chemotherapeutic agent. There is paucity of literature involving role of mitochondria in mediating CP-induced hepatic toxicity, and its underlying mechanism remains unclear. Oxidative stress is a well-established biomarker of the mitochondrial toxicity. Objective : This study evaluates the dose-dependent effects of CP-induced mitotoxicity under in vitro conditions, using mitochondria from rat liver. Materials and methods : The aim of our study was to determine the effect of CP with different concentrations in isolated liver mitochondria as an in vitro model. Results : CP exposure showed significantly compromised level of non enzymatic and enzymatic antioxidants with higher extent of lipid and protein oxidation. CP also caused significant alterations in the activity of respiratory chain enzymes (complex I–III and V) in liver mitochondria. Discussion and conclusion : It is suggested that mitochondria can be employed as a model for future investigations of anticancer drug-induced hepatotoxicity under in vitro conditions. Studies with selected pharmaceuticals and nutraceuticals might certainly play a definite role in deciphering cellular and molecular mechanisms of CP-induced hepatotoxicity and its amelioration.